2008
DOI: 10.5005/jcdp-9-6-25
|View full text |Cite
|
Sign up to set email alerts
|

A New Storage Medium for an Avulsed Tooth

Abstract: Aim The purpose of this study is to determine the efficacy of egg white in maintaining the viability of human periodontal ligament (PDL) cells on avulsed teeth. Methods and Materials The experimental media were: egg white, milk, Hanks’ Balanced Salt Solution (HBSS) as the positive control, and tap water as the negative control. The storage times were 1, 2, 4, 8, and 12 hours. Extracted premolar teeth of healthy individuals were rinsed in the media. After trypsinization and subsequent treatment in collagenase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
80
1
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(92 citation statements)
references
References 13 publications
2
80
1
7
Order By: Relevance
“…Especially, HBSS and GTE were most effective in preserving PDL cell viability for 24 hours because they could preserve the viability over 90%. The result of HBSS effectiveness is in agreement with other studies (8,21,32). Buttke and Trope (33) suggested that the storage of avulsed teeth in a medium containing one or more antioxidant components might increase the success rate of replantation.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Especially, HBSS and GTE were most effective in preserving PDL cell viability for 24 hours because they could preserve the viability over 90%. The result of HBSS effectiveness is in agreement with other studies (8,21,32). Buttke and Trope (33) suggested that the storage of avulsed teeth in a medium containing one or more antioxidant components might increase the success rate of replantation.…”
Section: Discussionsupporting
confidence: 88%
“…Extraoral time and storage medium are the critical factors responsible for prognosis of avulsed tooth (8,20,21). The longer the exposure of avulsed tooth to dry storage, the worse the prognosis of explantation is.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The International Association of Dental Traumatology (IADT) has recommended Hank's balanced salt solution (HBSS) as the storage medium of choice for avulsed teeth (2). Also other storage media for avulsed teeth, such as milk, ViaSpan â , saline, egg white, green tea extract, and propolis, have been reported (4)(5)(6)(7)(8). Although HBSS shows the best result among currently known storage media, at the time of accident, milk and coconut water are recommended as the most commonly available media most conveniently to patients (2,9).…”
mentioning
confidence: 99%